Targeted Cancer Therapy: Correlative Light-Electron Microscopy Shows RGD-Targeted ZnO Nanoparticles Dissolve in the Intracellular Environment of Triple Negative Breast Cancer Cells and Cause Apoptosis with Intratumor Heterogeneity (Adv. Healthcare Mater. 11/2016). - Othman,BA; Greenwood,C; Abuelela,AF; Bharath,AA; Chen,S; Theodorou,I; Douglas,T; Uchida,M; Ryan,M; Merzaban,JS; Porter,AE (Advanced Healthcare Materials, 2016)
On page 1310 J. S. Merzaban, A. E. Porter, and co-workers present fluorescently labeled RGD-targeted ZnO nanoparticles (NPs; green) for the targeted delivery of cytotoxic ZnO to integrin αvβ3 receptors expressed on triple negative breast cancer cells. Correlative light-electron microscopy shows that NPs dissolve into ionic Zn(2+) (blue) upon uptake and cause apoptosis (red) with intra-tumor heterogeneity, thereby providing a possible strategy for targeted breast cancer therapy. Cover design by Ivan Gromicho.